The EU and ASEAN: Strategic Partners in the Indo-Pacific Era - Driesmans, Igor; Visentin, Gabriele (AEI Insights, 2023)
In the context of increasing great power rivalries, the international system is being challenged and the geopolitical landscape getting more and more fragmented, leading to increasing risks of polarisation. These developments pose a genuine threat to multilateralism. Yet they can also offer an opportunity for strengthening the EU-ASEAN relations in the new Indo-Pacific era. Recently, the EU launched its Strategy for Cooperation in the Indo-Pacific, marking a major development for the EU’s relations with this immense and growing region. The Strategy serves as a recognition of the importance of the present and future engagement of the EU with the Indo-Pacific region as well as a strong proof of its existing stakes in the region’s prosperity and stability. The Strategy builds upon the EU’s extensive engagement in the region, consisting of bilateral and multilateral partnerships on a wide range of issues, such as sustainable development, trade, climate change, security, and green energy transition. At the same time, the Strategy focuses on upholding international law, including human rights and freedom of navigation. The new Strategy supports engagement with the ASEAN-led regional architecture, reiterates the EU’s support for ASEAN centrality and looks forward to the ambitious realisation of our EU-ASEAN Strategic Partnership. At the heart of the Indo-Pacific lies ASEAN and it comes as no surprise that the Strategy will be of major relevance for the future development of the EU-ASEAN relations, not least in building synergies with the ASEAN Outlook on the Indo-Pacific. We have solid foundations and a distinguished track record to build upon, robust economic and development links that make the EU one of ASEAN’s leading partners in the Indo-Pacific era. In fact, the EU- ASEAN relations play a pivotal role bringing stability, reliability, and opportunities for cooperation on a wide variety of issues to the wider region. As we are celebrating the 45th anniversary of the establishment of our relations in 2022, the EU and ASEAN will continue to strengthen relations to ensure high quality and sustainable connectivity along with advancing collaboration on research, innovation and digitalisation. Building back better and greener will be a key priority as the world is moving towards a post- pandemic recovery. Meanwhile, in the broader Indo-Pacific region, the EU and ASEAN can, should – and we believe will – continue to play an important role in promoting a rules-based order conducive to peace and stability.